Simple sequence repeat marker analysis reveals grouping of Pyrenophora tritici-repentis isolates based on geographic origin. Issue 2 (3rd April 2019) - Momeni, Hassan; Akhavan, Alireza; Aboukhaddour, Reem; Javan-Nikkhah, Mohammad; Razavi, Mohammad; Naghavi, Mohammad Reza; Strelkov, Stephen E.
Abstract: The population structure and genetic diversity of Pyrenophora tritici-repentis from hexaploid wheat were examined using 51 simple sequence repeat (SSR) markers designed to represent each chromosome of the pathogen. A total of 83 isolates representing races 1 and 2 of Ptr were analysed, including 35 isolates from Canada and 48 isolates from Iran. Isolates of the same two races but originating from different regions were compared in order to examine the effect of geographic origin on grouping. Most of the variation (91%) was observed within the examined populations and only 9% between populations. In addition, a moderate amount of gene flow (Nm = 2.8134) was found between populations. The average gene diversity and the percentage of polymorphic loci were estimated to be 0.2764 and 68.63%, respectively. Applying the unweighted pair group method with arithmetic mean procedure and Dice similarity coefficient revealed no obvious clustering of isolates based on race designation. In contrast, the grouping of isolates was consistent with geographic origin to some extent, with most isolates from Iran and Canada clustering separately regardless of race. These results indicate a link between geographic origin and the grouping of Ptr isolates, which could be detected by comparison of the same two races from two different regions. Previous research compared variable races, making it difficult to draw conclusions regarding the effect of geographic origin.